News consumption and green habits on the use of circular packaging in online shopping in Taiwan: An extension of the theory of planned behavior - Lee, Yi-Chih (Frontiers in Psychology, 2022)
The COVID-19 pandemic is far from over as outbreaks continue to spread around the world. The demand for packaging bags and cartons has also risen sharply in e-commerce shopping and takeaways because consumers have changed their shopping habits during the pandemic. The primary purpose of this study was to explore the factors prompting consumers to accept and use circular packaging when they shop online. From January to February 2022, a total of 373 online questionnaires were completed. The results showed that news consumption positively affected environmental attitudes, subjective norms, perceived behavioral control and circular packaging behavior intentions. Environmental attitudes, subjective norms, perceived behavioral control also affected the intention of circular packaging. Furthermore, news consumption influenced circular packaging behavioral intentions through environmental attitudes and green habits. Developing green habits in people's daily lives will be of great help in guiding consumers to engage in other sustainable behaviors that are beneficial to life.